Implementation of Sharia PSAK in The Management of Zakat in Mosques (Case Study on The Jami Grand Mosque of The Malang City) - Tanisah Nirmala Eka Suci; Suhendri, Hendrik; Muhammad Fauzy Emqi (International Research & Development for Human Beings (IRDH), 2025)
This study aims to analyze the application of Sharia Financial Accounting Standards Statement (PSAK) No. 109 in the management of zakat at the Masjid Agung Jami’ in Malang City, especially related to the recognition, measurement, presentation, and disclosure of zakat, infak, and alms funds. The method used in this research is qualitative, with data collection through interviews, observation, and documentation. The data obtained was analyzed using data reduction, data presentation, and verification techniques to get accurate results. The results of the study show that the management of zakat at the Majid Agung Jami’ (The Jami Grand Mosque of the Malang City) is not fully by PSAK No. 109, especially in the aspect of presenting financial reports that still use a cash basis. This study recommends transitioning from a cash basis to an accrual basis accounting system and implementing double bookkeeping to enhance transparency and accountability in zakat management following sharia accounting standards.